Food Prices, Wage Rates, and Inflation - Heflebower, Richard B. (The Review of Economics and Statistics, 1948)
Food prices, particularly those of grains, and the relationships among wages, prices, and incomes, occupy central roles in this the third of the post-VJ-Day upsurges in the commodity markets.' Did the partial failure of the grain crops in 1947 upset a situation that was approaching stability? Can wage rate increases bring such a simultaneous enlargement of consumer incomes and expenditures that price advances are not restrained? From consideration of these questions will emerge some points bearing on prospective price movements. i. Since VJ-Day the demand for food has been repeatedly misjudged. Instead of burdensome surpluses, we have had shortages. Each year Europe's needs have been greater than anticipated and our own postwar demand has been unexpectedly high.2 A year ago, following bumper crops, we had wage adjustments justified chiefly by what had happened to the working family's food budget. And now we are facing this familiar sequence again, but not solely because of the partial failure of the grain crops. Although the grain situation has had a direct effect on the prices of cereal products in 1947, neither meat nor dairy product supplies yet have been curtailed thereby.3 For the year as a whole (last few months projected), the Bureau of Agricultural Economics reports annual production rates for meats and milk above, and for eggs slightly below, the I946 rates. Rather than attempting the questionable task of making seasonal corrections in quarterly production rates, the gist of the comments of key persons in the government are reported here. The meat production rate up until the first of September clearly had not been reduced below what otherwise would have occurred as a result of high grain prices and reduced supplies. Since September i, the publicized reduction in hog weights has been offset approximately by larger numbers of livestock slaughtered, particularly of cattle, than would have occurred if grain supplies had been ample. While milk production has declined slightly as the year has advanced, the contribution of high grain prices to this development has been offset by an unusually long pasture season and a pressure to feed heavily from the large supply of soft corn. From such facts as these we come to the conclusion, and a disturbing conclusion it is, that this year's price increases for foods, except cereal products, and traceable chiefly to the growth of domestic consumer demand.4 Even had the grain crops been normal we would have experienced retail price movements for non-cereal foods similar to those which have occurred.5 2. In a manner similar to the misjudging of the postwar food situation, a pessimistic error has dominated much of the forecasting of the level of incomes and of consumer and business outlays. In part, such forecasts were built on t are reported here. The meat